2015
DOI: 10.7150/ijms.11694
|View full text |Cite
|
Sign up to set email alerts
|

Predicting One-Year Mortality in Peritoneal Dialysis Patients: An Analysis of the China Peritoneal Dialysis Registry

Abstract: This study aims to investigate basic clinical features of peritoneal dialysis (PD) patients, their prognostic risk factors, and to establish a prognostic model for predicting their one-year mortality. A national multi-center cohort study was performed. A total of 5,405 new PD cases from China Peritoneal Dialysis Registry in 2012 were enrolled in model group. All these patients had complete baseline data and were followed for one year. Demographic and clinical features of these patients were collected. Cox prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
3
10
1
Order By: Relevance
“…In addition, the other inflammatory markers were higher in the high FAR group. After adjusting for other factors, the Cox regression analysis showed that age, diabetes, hs‐CRP and total Kt/V were associated with mortality in PD patients, which is consistent with previous studies 19,20 . We further analysed the interaction among the FAR and other factors.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the other inflammatory markers were higher in the high FAR group. After adjusting for other factors, the Cox regression analysis showed that age, diabetes, hs‐CRP and total Kt/V were associated with mortality in PD patients, which is consistent with previous studies 19,20 . We further analysed the interaction among the FAR and other factors.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding that smoking was associated with mortality also remains consistent with previous literature, 28,34,35 which may be because smoking confers increased cardiovascular risk, as seen by the higher rates of congestive cardiac failure, peripheral vascular disease in smokers on dialysis. 36 Our study was neither powered nor designed to examine specific causes of mortality.…”
Section: Discussionsupporting
confidence: 92%
“…The association of age and diabetes mellitus with patient survival on PD is consistent with other studies, suggesting that these factors have clinical significance in predicting prognosis of PD patients. An association between smoking status and peritonitis has been noted in previous literature, which may be because cigarette smoke affects both cell‐mediated and humoral‐mediated immune responses, thereby increasing risk of infection .…”
Section: Discussionsupporting
confidence: 90%
“…Several risk scores for predicting all-cause mortality and cardiovascular mortality in patients undergoing dialysis have been reported previously [ 13 19 ]. One study has already developed and validated a risk model for cardiovascular mortality in patients undergoing PD.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction models for predicting the risk of all-cause and cardiovascular mortality among patients undergoing hemodialysis and PD have recently been developed [ 13 19 ]. However, there has been limited research regarding infection-related death in patients undergoing PD.…”
Section: Introductionmentioning
confidence: 99%